Association between metformin use and improved survival in patients with laryngeal squamous cell carcinoma. Issue 7 (29th January 2014) - Sandulache, Vlad C.; Hamblin, John S.; Skinner, Heath D.; Kubik, Mark W.; Myers, Jeffrey N.; Zevallos, Jose P.
Abstract Background Metformin use has been linked to improved cancer outcomes. The purpose of this study was to determine the impact of metformin on the survival of patients with laryngeal cancer. Methods We retrospectively reviewed 205 patients with a diagnosis of laryngeal squamous cell carcinoma (SCC). Results Patients taking metformin presented with more early‐stage tumors (T1 and T2) and less regional metastasis (N0; 81% metformin+ vs 50% metformin‐) compared to patients with diabetes not taking metformin. At last follow‐up, 76% of patients taking metformin were alive, compared to 41% for diabetics not on metformin and 51% for nondiabetics. Metformin users demonstrated increased disease‐free survival (DFS) and overall survival (OS) compared with nonmetformin users and nondiabetics. Conclusion Patients with diabetes taking metformin present with earlier stage disease and have more favorable clinical outcomes when compared to their diabetic counterparts and nondiabetics. Combined with previously published retrospective studies, our results suggest that prospective clinical trials evaluating the role of metformin in head and neck cancer are warranted. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1039–1043, 2014